Case report: bilateral Mooren ulcer in association with hepatitis C - Aaltonen V; Alavesa M; Pirilä L; Vesti E; Al-Juhaish M (BIOMED CENTRAL LTD, 2022)
Background: Mooren ulcer has been considered as an idiopathic autoimmune keratitis. However, it has been in some cases suggested to be associated with hepatitis C, although the evidence is very vague.Case presentation: We present a case of a man who was diagnosed with a primary Mooren ulcer in his right eye. The eye became blind despite of intensive treatment with local medications and extensive surgical procedures. After 10 years, the patient was diagnosed with the same disease, now in his left, previously healthy eye. There was no history that would suggest a secondary Mooren ulcer, but a chronic hepatitis C infection was detected. Treatment was targeted against hepatitis C (ribavirin and interferon) in addition to immunosuppressive medical and surgical treatment which resulted in a full and more than 6 years lasting remission of the disease.Conclusions: Whether the immunomodulatory and immunosuppressive medication against hepatitis C was the key reason for the good results in the treatment of the second eye, remains elusive. The causality of hepatitis C with respect to the pathogenesis of Mooren ulcer on this patient remains open, but should be considered as one of the possible etiological factors of the disease.